(untitled) (EAAE Joint Publishings, 2026)
This paper investigates the presence of forced labor in the supply chain of materials used in the design, construction, and delivery of buildings. While the Architecture, Engineering, and Construction (AEC) industry has conclusively acknowledged the very real costs of climate change, it has addressed the impacts of coercive labor practices and modern-day slavery in the making of buildings with far less commitment. This paper seeks to redress the situation by activating three research questions: how might we identify a common language in service to recognizing forced labor, what are available tools and sources currently at our disposal for addressing the problem, and what lessons can one learn from a case study that localizes the risk of forced labor in imported building products to the United States? In response, this paper identifies an internationally sanctioned vocabulary whose terms and definitions can help the building industry better characterize instances of forced labor while offering a critical review of currently available tools, protocols, and data resources of possible use to the industry. Whether in extracting raw materials, manufacturing building products, installing said products, or disposing of them as waste at the end of life, the health and safety of workers associated with building remain imperiled. As this reality can no longer be denied, this paper recognizes three aspects of a possible solution space, all the while remaining critical when confronted with the reality of forced labor as a deeply entrenched problem in the industry.